Prevention of Doxorubicin-Induced Autophagy Attenuates Oxidative Stress and Skeletal Muscle Dysfunction - Vivian Doerr; Ryan N. Montalvo; Oh Sung Kwon; Erin E. Talbert; Brian A. Hain; Fraser E. Houston; Ashley J. Smuder (MDPI AG, 2020)
Clinical use of the chemotherapeutic doxorubicin (DOX) promotes skeletal muscle atrophy and weakness, adversely affecting patient mobility and strength. Although the mechanisms responsible for DOX-induced skeletal muscle dysfunction remain unclear, studies implicate the significant production of reactive oxygen species (ROS) in this pathology. Supraphysiological ROS levels can enhance protein degradation via autophagy, and it is established that DOX upregulates autophagic signaling in skeletal muscle. To determine the precise contribution of accelerated autophagy to DOX-induced skeletal muscle dysfunction, we inhibited autophagy in the soleus via transduction of a dominant negative mutation of the autophagy related 5 (ATG5) protein. Targeted inhibition of autophagy prevented soleus muscle atrophy and contractile dysfunction acutely following DOX administration, which was associated with a reduction in mitochondrial ROS and maintenance of mitochondrial respiratory capacity. These beneficial modifications were potentially the result of enhanced transcription of antioxidant response element-related genes and increased antioxidant capacity. Specifically, our results showed significant upregulation of peroxisome proliferator-activated receptor gamma co-activator 1-alpha, nuclear respiratory factor-1, nuclear factor erythroid-2-related factor-2, nicotinamide-adenine dinucleotide phosphate quinone dehydrogenase-1, and catalase in the soleus with DOX treatment when autophagy was inhibited. These findings establish a significant role of autophagy in the development of oxidative stress and skeletal muscle weakness following DOX administration.